'Much land and water have I and my sweet companion run over…': newly discovered letters from Muzio Clementi to Gottfried Christoph Härtel. (25th November 2019) - Sala, Luca Lévi
Abstract: Three newly discovered letters from Muzio Clementi to Gottfried Christoph Härtel make a valuable addition to the known corpus of his correspondence with the Leipzig publisher. Held at the Staatsbibliothek zu Berlin (Mus. Slg. Härtel 28–30), these three letters originate in the early years of the second lengthy international trip that Clementi undertook, encompassing the end of 1804 and the first months of 1805, a period when he moved through Germany and settled for a while in Berlin before leaving for his honeymoon in Italy, prior to returning to Berlin. Since the bulk of the extant correspondence between Clementi and Härtel dates from between 1815 and 1822, these letters offer new knowledge about aspects of Clementi's friendship and business relationship with the German publisher, and about some details of Clementi's own private life.